An introduction to Reconstructing Proto-Bantu Grammar - Bostoen, Koen (My University, 2022)
This book is about reconstructing the grammar of Proto-Bantu, the ancestral language at the origin of the African linguistic family commonly known as Bantu. It is about how to retrieve the phonology, the morphology and the syntax the earliest Bantu speakers used to communicate with each other. In §1, I explain how this book came about. In §2, I offer a short presentation of its contents. In §3, I reflect critically on a number of methodological issues. Finally, in §4, I attempt to assess to what extent the new research presented in this volume requires a revision of Meeussen (1967).
Keywords: Proto-Bantu; Grammar; Language